Measuring the spin period of XMMU J004855.5-734946 during a large outburst - Vasilopoulos, Georgios (Chandra Proposal, 2015)
Spin periods of Be/X-ray binary (BeXRB) pulsars are important for probing their formation channels and the connection between orbital period and pulsar spin in XRBs (Knigge+ 2011). From the 120 BeXRBs in the SMC only 50% have known spin periods, with the majority of them measured during outburst with ToOs. From the remaining systems only 6 have a known orbital period. XMMU J004855.5-734946 is a BeXRB in the SMC (Haberl & Sturm 2016, XMM Lx (0.03-1)x10^35 erg/s) with a 36.43d orbital period (Atel#9198), but with no X-ray pulsations detected so far. On 06/24 a 37s Swift/XRT observation detected the system at Lx 10^37 erg/s (Atel#9197) following a marginal detection on 06/16 (Lx<5x10^36 erg/s) confirming the onset of a large outburst. A follow-up 1ks Swift ToO on 06/29 measures an Lx = 8.3x10^36 erg/s. This is a unique opportunity to measure the spin period of one of the few BeXRBs in the SMC with known orbital period but unknown spin period.